2017
DOI: 10.1097/jom.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

Job Demands, Job Resources, Burnout, Work Engagement, and Their Relationships

Abstract: More attention is needed to decrease burnout and increase work engagement, particularly in industry, service, and the public sector. The Job Demands-Resources model may be helpful in this regard, as it is valid across sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 32 publications
3
62
0
6
Order By: Relevance
“…However, the range of the items was broad (0.73–0.97) and this must be considered in regard to the two items mentioned above. Still, considering current research in the area of work-related psychosocial risk factors, we believe that items related to bullying and harassment [21, 69, 70] and job demands [71, 72] should be included in the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…However, the range of the items was broad (0.73–0.97) and this must be considered in regard to the two items mentioned above. Still, considering current research in the area of work-related psychosocial risk factors, we believe that items related to bullying and harassment [21, 69, 70] and job demands [71, 72] should be included in the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…All five job resources were negatively related to exhaustion among the permanent and temporary employees, with the exception that job control was the only job resource significantly and negatively associated with exhaustion among the temporary agency employees. Previous studies comparing different employee groups have similarly found the same job demands and resources to be equally associated with outcomes such as work engagement, burnout [52], task satisfaction, work-related fatigue and organizational commitment [53] in different sectors.…”
Section: Theoretical Implicationsmentioning
confidence: 93%
“…In light of the Job Demands–Resources model [ 6 , 25 ], there is a growing consensus on the influence of work environment characteristics on engagement [ 26 , 27 , 28 ]. Certain job demands such as role ambiguity and role conflict have constituted an active field of research in educational settings [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%